A case of guillain-barré syndrome associated with post-covid infection during 2nd wave of coronavirus in india (Indian Journal of Case Reports, 2021)
The novel coronavirus-COVID-19 was detected in Wuhan city of Hubei Province in China on December 31, 2019. Coronaviruses are known to infect multiple organ systems, with respiratory complications being the most obvious symptoms. Although, neurological manifestations are quite rarely reported in cases of COVID-19. In this report, we present the case of a 57-year-old male patient reported with complaints of acute progressive symmetric quadriparesis and recently recovered from COVID-19. Two weeks prior to hospitalization, the patient suffered from cough and fever. The reverse transcriptase-polymerase chain reaction test for COVID-19 infection was positive. Electrodiagnostic tests showed that the patient had acute motor and sensory axonal neuropathy variant of Guillain-Barré Syndrome (GBS). COVID-19 virus stimulates the inflammatory cells and as a result, creates immune-mediated processes. GBS is an immune-mediated disorder. It is not clear whether COVID-19 infection induces the production of antibodies against specific gangliosides. Further investigations should be conducted in regards to the mechanism of GBS in patients with COVID-19 in the future.